HIV testing in nonhealthcare facilities among adolescent MSM. (1st July 2017) - Marano, Mariette R.; Stein, Renee; Williams, Weston O.; Wang, Guoshen; Xu, Songli; Uhl, Gary; Cheng, Qi; Rasberry, Catherine N.
Abstract : Objectives: To describe the extent to which Centers for Disease Control and Prevention (CDC)-funded HIV testing in nonhealthcare facilities reaches adolescent MSM, identifies new HIV infections, and links those newly diagnosed to medical care. Methods/design: We describe HIV testing, newly diagnosed positivity, and linkage to medical care for adolescent MSM who received a CDC-funded HIV test in a nonhealthcare facility in 2015. We assess outcomes by race/ethnicity, HIV-related risk behaviors, and US geographical region. Results: Of the 703 890 CDC-funded HIV testing events conducted in nonhealthcare facilities in 2015, 6848 (0.9%) were provided to adolescent MSM aged 13–19 years. Among those tested, 1.8% were newly diagnosed with HIV, compared with 0.7% among total tests provided in nonhealthcare facilities regardless of age and sex. The odds of testing positive among black adolescent MSM were nearly four times that of white adolescent MSM in multivariable analysis (odds ratio = 3.97, P  < 0.001). Among adolescent MSM newly diagnosed with HIV, 67% were linked to HIV medical care. Linkage was lower among black (59%) and Hispanic/Latino adolescent MSM (71%) compared with white adolescent MSM (88%). Conclusion: CDC-funded nonhealthcare facilities can reach and provide HIV tests to adolescent MSM and identify new HIV infections; however, given the low rate of HIV testing overall and high engagement in HIV-related risk behaviors, there are opportunities to increase access to HIV testing and linkage to care for HIV-positive adolescent MSM. Efforts are needed to identify and address the barriers that prevent black and Hispanic/Latino adolescent MSM from being linked to HIV medical care in a timely manner.